2007
DOI: 10.2174/092986707782360150
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Peptides: The Future of Patient Management in Systemic Rheumatic Diseases?

Abstract: Since the first description of self-reactive antibodies in systemic autoimmune rheumatic diseases, many autoantigens have been identified as useful diagnostic biomarkers in clinical immunology. Among the autoantigens, double-stranded desoxoribonucleic acid (dsDNA), the Smith antigen (Sm), topoisomerase-I (topo-I), proliferating cell nuclear antigen (PCNA), and others were described as hallmark targets of systemic autoimmune diseases. The detection of the corresponding autoantibodies can be performed with a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…Further, it is well known that it is important to follow patients longitudinally for many years because one autoimmune condition can evolve to another [40] and several studies have reported overlap syndromes of SSc and other diseases such as SLE and RA [41]. Perhaps of more clinical importance, ACA have been reported to precede the diagnosis of SSc and have therefore been proposed as a biomarker to predict the onset of SSc [42,43]. Last but not least, the possibility of physician-based diagnostic error is also a potential complicating factor.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is well known that it is important to follow patients longitudinally for many years because one autoimmune condition can evolve to another [40] and several studies have reported overlap syndromes of SSc and other diseases such as SLE and RA [41]. Perhaps of more clinical importance, ACA have been reported to precede the diagnosis of SSc and have therefore been proposed as a biomarker to predict the onset of SSc [42,43]. Last but not least, the possibility of physician-based diagnostic error is also a potential complicating factor.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison in SLE, a prototype SARD, more than 150 aAb specificities have been described 13 . Further, some aAbs have been shown to predict the onset of autoimmune conditions for up to decades before full clinical expression, such as anti‐Ro or anti‐double‐stranded DNA (dsDNA) aAbs; 14 others, such as anti‐chromatin, anti‐dsDNA, and anti‐acetylcholine receptor aAbs, are believed to be pathogenic, while there is evidence that some aAbs may be protective against pathogenic processes 15–18 …”
Section: Autoantibodiesmentioning
confidence: 99%
“…We anticipated that such a new quantitative diagnostic assay might be more representative of the immunological state of the disease, a feature which in turn might benefit patients. To this end, we tested recombinant over-expressed PLA 2 R as a potential target on an addressable laser bead immunoassay (ALBIA) diagnostic platforms and examined overlapping PLA 2 R 15mer peptides representing the full length protein as an approach to identifying a specific epitope which could then be adapted to an improved immunoassay by using smaller peptides [23].…”
Section: Introductionmentioning
confidence: 99%